Pembinaan dan Upaya Meningkatkan Kreativitas Ekonomi Masyarakat serta Sertifikasi Halal di Desa Penebal - Irawan Fahrudin Mz; M.Ashsubli; Mashuri Mashuri; Imam Rohadi; Muhammad Yusuf; Kristin Lecintiva Agustina; Siti Mariam; Febriyenti Maulydya; Muhammad Israf Setiawan; Asri Yullasnyah; Soma Gustianda (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
With PKM, this is a place to utilize existing knowledge. various innovation and creativity efforts as well as the thoughts of the lecturers can make the local community more creative too. As well as how halal certification is carried out and there are several issues that need more attention, including:1. Lack of community skills in creativity,2. Lack of public awareness of the importance of innovation in maintaining economy, 3.. Lack of knowledge regarding how to carry out appropriate innovation with the surrounding economic conditions, as well as the problem of understanding halal certification